2009
DOI: 10.1017/s1743921310005594
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity Evolution of AGNs

Abstract: Abstract. Chemical properties of AGNs and their redshift evolution are of interest to understand the star-formation history of AGN host galaxies and the co-evolution between galaxies and supermassive black holes (SMBHs). One important observational clue on this issue is a tight correlation between the AGN luminosity and the metallicity of the broad-line region. Surprisingly this relation shows no redshift evolution, even up to z ∼ 6. This correlation is attributable mainly to the positive correlation between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At present, the better-defined correlation of the metal content appears to be with luminosity (Shin et al 2013). This correlation is especially strong, and is confirmed by diagnostics based on narrow lines (Nagao et al 2006a(Nagao et al , 2010. Dietrich et al (2009) found that the gas metallicity of the broad-line region is supersolar with 3 Z/Z in luminous, intermediate-redshift quasars, from measurements of the Niii]λ1750/Oiii]λ1663 and Nvλ1240/Civλ1549 emission line ratios.…”
Section: Possible Interpretation Of Lower Chemical Abundance At High Zmentioning
confidence: 73%
“…At present, the better-defined correlation of the metal content appears to be with luminosity (Shin et al 2013). This correlation is especially strong, and is confirmed by diagnostics based on narrow lines (Nagao et al 2006a(Nagao et al , 2010. Dietrich et al (2009) found that the gas metallicity of the broad-line region is supersolar with 3 Z/Z in luminous, intermediate-redshift quasars, from measurements of the Niii]λ1750/Oiii]λ1663 and Nvλ1240/Civλ1549 emission line ratios.…”
Section: Possible Interpretation Of Lower Chemical Abundance At High Zmentioning
confidence: 73%
“…With this large sample and the composite spectra with high signal-to-noise ratio (S/N), we can get a precise measurement of line ratio to estimate the metallicity of quasar BLR and then get a better statistical investigation for the evolution of metallicity in a wide range of BH mass and bolometric luminosity. We mainly focus on the metallicity of BLR in this work instead of narrow line region (NLR) which is supposed to trace the spatial scale (Bennert et al 2006a,b) and the enrichment history of quasar host galaxies (Nagao et al 2010). This is because that some typical NLR metallicity indicators, like [N II]/Hα (Ludwig et al 2012;Du et al 2014), has lines that exceed the wavelength coverage of SDSS spectra, especially at higher redshift.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this problem, it is not easy to do sufficient statistical analysis on NLR with a wide redshift range comparing to BLR. The metallicity in quasar BLR can be affected by local starbursts at the center of quasar host galaxies (Nagao et al 2010), so it may not well present the global metallicity in host galax-ies. But comparing the metallicity in the quasar BLR and its host galaxies can provide crucial information on the different history of star formation and metallicity enrichment in different parts of the galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…under the assumption of constant density (n 9 is in units of 10 9 cm −3 ). The metallicity is scaled to 10Z , appropriate for highly accreting quasars detected at high redshift [36,41,47,48]. The corresponding outflow kinetic power, with outflow v in units of 5000 km s −1 , is:…”
Section: Feedback Effects Of Accreting Black Holesmentioning
confidence: 99%